New Ways to Study the Effects of Physical Factors on the Organism Provide the Highest Efficiency of Treatment - Bitsoev, Vladmimir Dodtievich (Highlights on Medicine and Medical Research Vol. 3, 2021)
This work is dedicated to the new approach in applying physical factors in complex patient therapy. Based on experimental research data the author believes it is necessary to reconsider technical characteristics and exposition of physiotherapeutic factor influencing on the organism taking into account nosological form of disease and individual patient’s specifics. In this regard the author developed new tasks of the clinical physiotherapy and suggested seven principles of new classification of physical factors in complex patient therapy. On the basis of the research the author provided new concepts in medicine: 1) human organism as “biological scanning tunneling microscope”; 2) human as a part of “Nature” corresponds to universe general law: “singularity and indivisibility of time, matter and form”, as well as the forces of their interaction under constant endless motion. The effectiveness and the safety of physiotherapy eventually depend on the doctor’s ability to evaluate all these factors correctly. It is necessary to be based on the deep knowledge of both clinical medicine and experimental physiotherapy.